A Comparative Study of Political Communication in Televised Pre-Election Debates in Poland and the United States of America - Hinton, Martin; Budzyńska-Daca, Agnieszka (Research in Language, 2019)
This paper combines quantitative and qualitative methodologies to study the persuasive strategies employed by candidates taking part in televised pre-election debates in Poland and the United States between 1995 and 2016. First, the authors identify the key strategies and calculate the frequency with which they are used by individual candidates. This allows for numerical comparisons between politicians in the two polities, as well as between winners and losers, and candidates of the right and the left politically. These statistical results led the authors to look more closely at the individual styles of two contrasting debaters. We conclude that the rhetorical landscape of political communication does not differ greatly between the two countries; although the data suggest noticeable differences in the approach of political parties and between individuals.